Prognostic factors to succeed in surgical treatment of chronic acromioclavicular dislocations - Barth, J.; Duparc, F.; Baverel, L.; Bahurel, J.; Toussaint, B.; Bertiaux, S.; Clavert, P.; Gastaud, O.; Brassart, N.; Beaudouin, E.; De Mourgues, P.; Berne, D.; et al. (Orthopaedics & traumatology, surgery & research, 2015)
Treatment of chronic acromioclavicular joint dislocation (ACJD) remains a poorly known and controversial subject. Given the many surgical options, it is not always easy to determine which steps are indispensable. This article reports a multicenter prospective study. The clinical and radiological follow-up involved a comparative analysis of the preoperative and postoperative data at 1 year, including pain (visual analogue scale), subjective functional incapacity (QuickDASH), and the objective Constant score, as well as a comparative analysis of vertical and horizontal movements measured on simple x-rays. Based on a series of 140 operated ACJDs, we included 24 chronic ACJDs. The mean time to surgery was 46 weeks (range, 1 month to 4 years). The patients’ mean age was 41 years, with a majority of males (75%), 72% of whom participated in recreational sports. Professionally, 40% of the subjects had jobs involving manual labor. We noted 40% grade III, 24% grade IV, and 36% grade V injury according to the Rockwood classification. In 92% of cases, coracoclavicular stabilization was provided by a double button implant, reinforced with a biological graft in 88% of the cases. In 29%, millimeters to centimeters of the distal clavicle were resected and acromioclavicular stabilization was associated in 54%. We observed complications in 33% of the cases. At 1 year postoperative, 21 patients underwent clinical and radiological follow-up (87.5%). Only 35% of the patients were satisfied or very satisfied, whereas 100% of them would recommend the operation. Full-time work was resumed in 91% of the cases and all sports could be resumed in 86%. The pre- and postoperative values at 1 year changed as follows: the mean Constant score improved from 61 to 87 (p=0.00002); the subjective QuickDASH score decreased from 41 to 9 (p=0.00002); and radiologically significant reduction of the initial displacement was observed in the vertical plane (p<10−3) and the horizontal plane (p=0.022). In this study, the favorable prognostic factors found were: time to surgery less than 3 months (p=0.02), associated acromioclavicular stabilization, and postoperative immobilization with a sling extended to 6 weeks. However, resection of the distal clavicle did not influence the final result. Level II prospective non-randomized comparative study.